BECOME A UNITY SHADERS GURU create advanced game visuals using code and graphs - Pêcheux, Mina (Packt Publishing Ltd., 2023)
Discover a range of advanced shading techniques to beautify your 2D/3D game projects with Unity 2022 Purchase of the print or Kindle book includes a free PDF eBook Key Features Discover the new shader tools such as URP and Shader Graph to work in HLSL code or with visual node-based editing Learn advanced tricks to optimize your rendering pipeline Explore various concepts to create a variety of 2D and 3D game shaders Book Description Do you really know all the ins-and-outs of Unity shaders? It's time to step up your Unity game and dive into the new URP render pipeline, the Shader Graph tool, and advanced shading techniques to bring out the beauty of your 2D/3D game projects! Become a Unity Shaders Guru is here to help you transition from the built-in render pipeline to the SRP pipelines and learn the latest shading tools. With it, you'll dive deeper into Unity shaders by understanding the essential concepts through practical examples. First, you'll discover how to create a simple shading model in the Unity built-in render pipeline, and then in the Unity URP render pipeline and Shader Graph while learning about the practical applications of both. You'll explore common game shader techniques, ranging from interior mapping to adding neon outlines on a sprite or simulating the wobble of a fish. You'll also learn about alternative rendering techniques, like Ray Marching. By the end of this book, you'll have learned to create a wide variety of 2D and 3D shaders with Unity's URP pipeline (both in HLSL code and with the Shader Graph tool), and be well-versed with some optimization tricks to make your games friendly for low-tier devices as well. What you will learn Understand the main differences between the legacy render pipeline and the SRP Create shaders in Unity with HLSL code and the Shader Graph 10 tool Implement common game shaders for VFX, animation, procedural generation, and more Experiment with offloading work from the CPU to the GPU Identify different optimization tools and their uses Discover useful URP shaders and re-adapt them in your projects Who this book is for This book is for technical artists who have worked with Unity and want to get a deeper understanding of Unity's render pipelines and its visual node-based editing tool. Seasoned game developers who are looking for reference shaders using the recent URP render pipeline will also find this book useful. A basic level of programming experience in HLSL, Unity, its layout, and its basic usage is a must.